Output-Feedback Control for a Class of Stochastic High-Order Feedforward Nonlinear Systems with Delay. (27th April 2014) - Ma, Qian; Jiao, Ticao; Cui, Guozeng
Abstract : The problem of global output-feedback stabilization for a class of stochastic high-order time-delay feedforward nonlinear systems with different power orders is investigated. By combining the adding one power integrator technique with the homogeneous domination approach, an output-feedback controller design is proposed, which ensures the global asymptotical stability in probability of the closed-loop system.